G(x) = 2x + 2
g(a + h) - g(a) = 2(a+h) + 2 - (2(a) + 2)
g(a + h) - g(a) = 2a + 2h + 2 - 2a - 2
g(a + h) - g(a) = 2h + 2 - 2
g(a + h) - g(a) = 2h
Your final answer is a. 2h.
Answer:
Squaring both the sides, we get a quadratic and solving it, we find that the possible values of x are -7 and -4.
Step-by-step explanation:
The expression can be written as √(x+8) - 6 = x. Take 6 on the other side and square both the sides.
[√(x + 8)]² = (x + 6)²
x + 8 = x² + 12x + 36
x² + 11x + 28 = 0
x² + 7x + 4x + 28 = 0
(x + 7)(x + 4) = 0
x = -7 and x = -4
The possible values of x are -7 and -4.
For more explanation, refer the following link:
brainly.com/question/10572241
#SPJ10
Answer:
5 cups
I would appreciate Brainliest but no worries.
Answer:T-3, -1 applied to a rectangle hm
Step-by-step explanation:
Well why don't you just GOOGLE IT
9x² - 49
(3x)² - (7)²
= (3x + 7)(3x - 7)
This type of factoring is called Difference of Two Squares
where x² - y² = (x + y)(x - y)